Observasi Diaphragm Wall Metode Cut Off Wall sebagai Penanganan Rembesan Wilayah Waduk Cengklik. - Samad, Nur Jannati (Jurnal Proyek Teknik Sipil, 2023)
Cengklik Reservoir is one of the tourist attractions in the Boyolali area. Functionally, the Cengklik reservoir is used as a water reservoir or storage area as well as a source of water for the needs of the surrounding community and to supply rice fields. Based on observations, the reservoir has decreased in function, namely seepage is found. One of the methods applied for the handling of seepage is the foundation structure in the form of a diaphragm wall. Observations were started by collecting data (pumping test data and drawings of the diaphragm wall structure). The results obtained for the total diaphragm wall foundation with a depth of 16 m with a depth of excavated soil of 16 m. Specifications for the diaphragm wall plan with a land area of 375m. Diaphragma wall (slurry wall) is a type of plastic concrete retaining wall with a foundation that has very strong rigidity, low vibration during construction, and has a waterproof function. Diaphragama wall provides less seepage effect than other methods such as secant pile. The secant pile only has the same use but differs in area. Cut off wall is a method of excavation work, surrounded by excavated land such as a guide wall. Insulation or retaining water flow on large dam foundations is usually done by the Cut of wall method. This method is suitable for excavation work which is quite deep and dense soil area